Design, synthesis and biological evaluation of a novel colchicine-magnolol hybrid for inhibiting the growth of Lewis lung carcinoma in Vitro and in Vivo - Li, Zhiyue; Hu, Shengquan; Pu, Liu-Yang; Li, Ziwen; Zhu, Guanbao; Cao, Yongkai; Li, Limin; Ma, Yucui; Liu, Zhanyan; Li, Xinping; Liu, Guangjie; Chen, Keji; et al. (Frontiers in Chemistry, 2022)
Colchicine is a bioactive alkaloid originally from Colchicum autumnale and possesses excellent antiproliferative activity. However, colchicine-associated severe toxicity, gastrointestinal side effects in particular, limits its further therapeutic use. In the current study, we thus designed and synthesized a novel hybrid (CMH) by splicing colchicine and magnolol, a multifunctional polyphenol showing favorable gastrointestinal protection. The antitumor activity of CMH in Lewis lung carcinoma (LLC) was then evaluated in vitro and in vivo. Biologically, CMH inhibited the growth of LLC cells with an IC50 of 0.26 μM, 100 times more potently than cisplatin (26.05 μM) did. Meanwhile, the cytotoxicity of CMH was 10-fold lower than that of colchicine in normal human lung cells (BEAS-2B). In C57BL/6 mice xenograft model, CMH (0.5 mg/kg) worked as efficacious as colchicine (0.5 mg/kg) to inhibit tumor growth and 2 times more potently than cisplatin (1 mg/kg). In terms of mortality, 7 out of 10 mice died in colchicine group (0.75 mg/kg), while no death was observed in groups receiving CMH or cisplatin at 0.75 mg/kg. Mechanistic studies using Western blot revealed that CMH dose-dependently suppressed the protein expression of phosphorylated ERK. Molecular docking analysis further indicated that CMH was well fitted in the colchicine binding site of tubulin and formed several hydrogen bonds with tubulin protein. These results enable our novel hybrid CMH as a potential antineoplastic agent with lower toxicity, and provide perquisites for further investigation to confirm the therapeutic potentiality of this novel hybrid.